PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT SON DUCT SEJAHTERA - Rosita, Della; Imaroh, Tukhas Shilul (Universitas Mercu Buana, 2024)
This study aims to determine the effect of compensation on employee performance, work discipline on employee performance, and organizational culture on employee performance. This research is a type of causal associative research that aims to analyze the relationship between one variable and another or how a variable affects other variables. The population in this study are employees who work at PT Son Duct Sejahtera. The sampling method used saturated sampling technique with a total sample of 55 respondents. Primary data was collected by distributing questionnaires, secondary data was taken from the company. The data analysis method used is the Variance Based Structural Equation Model - Partial Least Square (Smart-PLS). The results showed that compensation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and organizational culture has a positive and significant effect on employee performance.